Exploratory study on the handling of childbirth assistance during the covid-19 pandemic - Sa'adah Mujahidah; Tutut Yuliani Lestari; Dewi Mayangsari; Durrotun Munafiah (Link Journal of Midwivery, 2025)
Background: Health professionals who handled deliveries with confirmed COVID-19 reported that they followed government regulations while adhering to the health protocol and wearing PPE level 3 to prevent exposure to the virus. This was done while taking into consideration the delivery services' capacity for health security, health services, efforts to promote and prevent, and response management. Objectives: To learn about the management of aid during the COVID-19 pandemic in hospitals, public health centers, and independent practice midwives. Methods: This research is qualitative. The research was conducted from July to August of 2022. In this study, 13 midwives who worked in hospitals and with mothers giving birth were chosen via snowball sampling. The six participants in this study were one village midwife, Banjarsari Sayung, the head of the panel room at Sunan Kalijaga Demak Hospital, and the team leaders for midwife coordination at Wonosalam 1 and Wonosalam 2 health centers. An in-depth interview instrument was used in this investigation. Before proceeding to the deductive phase, run the data through the normal inductive analysis technique. Results: The interviews revealed that the local government plays an important role in strengthening the health security capacity and the service capacity of all facilities to ensure that maternity mothers are not exposed to COVID-19. Response management takes the form of questionnaires and suggestion boxes. Conclusion: security capability in terms of service, the capacity of the services offered is of high quality, and response management takes the form of measurement tools such as surveys and suggestion boxes.